Rivers lost, rivers regained : rethinking city-river relations - Knoll, Martin; Lübken, Uwe; Schott, Dieter (History of the urban environment., 2017)
"Rivers Lost, Rivers Regained discusses how cities have gained control and exerted power over rivers and waterways far upstream and downstream; how rivers and floodplains in cityscapes have been transformed by urbanization and industrialization; how urban rivers have been represented in cultural manifestations, such as novels and songs; and discusses more recent strategies to redefine and recreate the place of the river within the urban setting"--Provided by publisher.